Dissecting the heritable risk of breast cancer: From statistical methods to susceptibility genes - Fanfani, Viola; Zatopkova, Martina; Harris, Adrian L; Pezzella, Francesco; Stracquadanio, Giovanni (Seminars in cancer biology, 2021)
Decades of research have shown that rare highly penetrant mutations can promote tumorigenesis, but it is still unclear whether variants observed at high-frequency in the broader population could modulate the risk of developing cancer. Genome-wide Association Studies (GWAS) have generated a wealth of data linking single nucleotide polymorphisms (SNPs) to increased cancer risk, but the effect of these mutations are usually subtle, leaving most of cancer heritability unexplained. Understanding the role of high-frequency mutations in cancer can provide new intervention points for early diagnostics, patient stratification and treatment in malignancies with high prevalence, such as breast cancer. Here we review state-of-the-art methods to study cancer heritability using GWAS data and provide an updated map of breast cancer susceptibility loci at the SNP and gene level.
Keywords: Cancer; celogenomová asociační studie; Cancer risk; GWAS; Polymorphism, Single Nucleotide; Humans; Biomarkers, Tumor; jednonukleotidový polymorfismus; Female; lidé; Models, Statistical; nádorové biomarkery; Breast Neoplasms; ženské pohlaví; Heritability; Genetic Predisposition to Disease; prognóza; genetická predispozice k nemoci; nádory prsu; statistické modely; Genome-Wide Association Study; Prognosis; SNP